Courting colonialism: considering litigation as an act of Citizenship in Colonial Burma - Venker, Matthew (Citizenship studies, 2024)
Litigants in colonial Burma were ascribed a set of personal law codes according to their race and religion. Women were generally given the personal law status of their fathers, which imposed disadvantages on the daughters of mixed Chinese Burmese couples. In this paper, I identify efforts mixed women litigants made to reinscribe their personal law by mobilizing claims about the communities they belonged to outside the court as 'acts of citizenship'. I describe points of rapprochement between theoretical trajectories that locate citizenship in- and outside the law. I adapt Mamood Mamdani's classic distinction of citizen/subject to theorize the potential for enacting citizenship under conditions of colonial subjecthood.